Decomposing Changes in Income Inequality into Vertical and Horizontal Redistribution and Reranking, with Applications to China and Vietnam - Wagstaff, Adam (World Bank, Washington, DC, 2012)
It is acknowledged that the lack of any systematic link between growth and income inequality does not necessarily mean that economic growth is not accompanied by major changes in the underlying income distribution. The author uses a method devised to decompose the redistributive effect of a tax to analyze the extent to which vertical redistribution associated with changing incomes over time is offset or reinforced by horizontal redistribution and re-ranking. He uses panel data from China and Vietnam over a period when both countries grew spectacularly as they transitioned from planned to market economies, and yet experienced smaller annual percentage increases in income inequality. The results suggest that substantial amounts of horizontal redistribution and re-ranking in both China-and to a lesser extent Vietnam-more than offset pro-poor vertical redistribution. Without the horizontal redistribution and re-ranking, the Gini coefficient for China might have fallen between 1989 and 1997-substantially so.